The Comparison and Analysis of BDS NRTK between DD and UD Models. Issue 2 (26th April 2018) - Tu, Rui; Liu, Jinhai; Lu, Cuixian; Zhang, Rui; Zhang, Pengfei; Lu, Xiaochun
Abstract: The BeiDou Navigation Satellite System (BDS) Network Real Time Kinematic (NRTK) position algorithm with both Double‐Differenced (DD) model and Un‐Differenced (UD) model is investigated in this study. This algorithm is realized and validated with experimental BDS data collected at four regional stations. For the experiment within the regional network, a short convergence time for each model is considered. The results show that the BDS NRTK is able to provide positioning service with accuracy at the cm level. Theoretically, UD‐NRTK and DD‐NRTK are equivalent to each other. The small differences found between the DD and UD models in this study can be clarified in that the error correction for the DD model is more precise than that for the UD model, resulting in faster solution convergence in the DD model. However, the noise of the DD model is two times of the UD model, which usually leads to larger final RMS of positioning accuracy for the DD model. Copyright © 2018 Institute of Navigation